Causes of musculoskeletal complaint on carving crafters in Bantul - Rahmat Hidayat; Widodo Hariyono; Adi Heru Sutomo (Berita Kedokteran Masyarakat (BKM), 2016)
Causes of musculoskeletal complaint on carving crafters in BantulPurposeThe purpose of this study was to determine the factors causing musculoskeletal disorders in furniture carvers in Bantul. These factors are age, length of service, work stress and smoking habit.MethodsA cross-sectional study was conducted by distributing questionnaires to 56 respondents in a furniture carving business in Bantul. The independent variables were age, years of service, work stress, and smoking habits, while the dependent variable was a musculoskeletal disorder. Measurement of musculoskeletal disorder used a questionnaire, and Nordic Body Map while work stress measurement used a work stress indicator questionnaire.ResultsThe study found that there was a significant correlation between age and work stress with musculoskeletal complaints in furniture craftsmen in Bantul, while the working period and smoking habit did not significantly influence the musculoskeletal disorder in furniture crafters in Bantul.ConclusionAge and occupational stress are factors that affect musculoskeletal complaints, while the habit of work and smoking habit did not have a significant effect on the occurrence of musculoskeletal complaints in furniture crafters in Bantul. Work rotation and workspace design need to be done properly to minimize the risk of musculoskeletal problems in furniture crafters in Bantul.